Pemeliharaan Saluran Sistem Drainase Melalui Manajemen Pastisipatif di RT 7 Kelurahan Legok, Kota Jambi - Lailal Gusri; Nurza Purwa Abiyoga; Abdul Manab; Tri Syukria Putra; M. Nuklirullah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Drainage systems require maintenance to ensure the proper functioning of the constructed system. If maintenance is not maintained or is inadequately maintained, problems with drainage capacity will occur. Community participation in drainage management can foster human-environmental relations through mutual cooperation. The goal is to increase understanding of the importance of community participation in drainage maintenance through participatory management. The community service method facilitates understanding and visits to drainage areas, and offers solutions on how participatory management works in the community. The results of community participation are an important component for successful drainage maintenance and community flood preparedness. The residents of RT 07, Legok Village, were very impressed and inspired a desire to participate in drainage system maintenance to prevent garbage accumulation and siltation.